2016
DOI: 10.3109/09638288.2016.1162853
|View full text |Cite
|
Sign up to set email alerts
|

H-GRASP: the feasibility of an upper limb home exercise program monitored by phone for individuals post stroke

Abstract: Purpose: To investigate the feasibility of a phone-monitored home exercise program for the upper limb following stroke. Methods: A pre-post double baseline repeated measures design was used. Participants completed an 8-week home exercise program that included behavioural strategies to promote greater use of the affected upper limb. Participants were monitored weekly by therapists over the phone. The following feasibility outcomes were collected: Process (e.g. recruitment rate); Resources (e.g. exercise adheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 40 publications
1
26
0
1
Order By: Relevance
“…In our study, dexterity was included in the assessment, showing excellent interreliability. Programs that can monitor upper limb function by phone or the Internet have been reported to be suitable for rural settings where clients may have limited access to community services . However, regular access to the Internet is lower among rural compared to urban residents .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, dexterity was included in the assessment, showing excellent interreliability. Programs that can monitor upper limb function by phone or the Internet have been reported to be suitable for rural settings where clients may have limited access to community services . However, regular access to the Internet is lower among rural compared to urban residents .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, home-based exercise programmes have been increasingly developed to promote exercise and physical activity among community-dwelling stroke survivors [11][12][13][14][15]. Home-based exercise programmes can result in improved function of stroke survivors, including better balance and more involvement in activities of daily living [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, substantial gains in health-related quality of life during inpatient stroke rehabilitation may be followed by equally substantial declines in the 6 months after discharge [ 4 ]. Multiple studies have shown, however, that supported discharge combined with at home rehabilitation services does not compromise clinical inpatient outcomes [ 5 - 7 ] and may enhance recovery in subacute stroke patients [ 8 ]. Hence, it is essential that new approaches are deployed that help to manage chronic conditions associated with stroke, including domiciliary interventions [ 9 ] and the augmentation of current rehabilitation approaches in order to enhance their efficiency.…”
Section: Introductionmentioning
confidence: 99%